Health care expenditure and income in the European countries: evidence from panel data - de Mello-Sampayo, F.; Vale, S. (International Conference of the ERCIM WG on COMPUTING & STATISTICS (ERCIM'10), 2010)
The economic relationship between health care expenditure and income using a panel of european countries observed over the 1990s is considered. In particular, the non-stationarity and cointegration properties between health care spending and income is studied. This is performed in a panel data context controlling for both cross-section dependence and unobserved heterogeneity. Heterogeneity is handled through fixed effects in a panel model. The findings suggest that health care is a necessity rather than a luxury, with an elasticity much smaller than expected.